Antimicrobial activity of petroleum ether extracts from leaves, seeds and roots of Zygophyllum fabago L. towards some microorganisms - AL-Qaissi, E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study was aims to evaluate the antimicrobial acttvtty of petroleum ether extracts from leaves , seeds and root of Zygophyllum fabago , against several microorganisms including gram negative bacteria (Pseudomonas aeruginosa & Escherichia coli), gram positive bacteria (Staphylluwccus aureus & Bacillus subtilis), in addition to yeast (Candida albicans). While the results of sensitivity of the microorganisms to words petroleum ether extracts showed different activity , petrolewn ether extract of seeds showed more antimicrobial activity compared to the other extracts , followed by leaves and roots extracts. Concerning the bacterial isolates B. subtilis was more sensitive, its growth inhibited by leaves, seeds and roots extract of Z. fabago, MIC was ( IOd·20) mgfml, followed by S. aureus MIC was (20d 30) mgfml, then E. coli was (30·10·50) mgjml, where as P. acruginosa MIC was (50·20·30) mg/ml. finally C. albicans which was the most resistant for all extracts (leaves, seeds, roots) and MIC was (50•20•30) mgfml. Analysis of petrolewn ether extracts from leaves, seeds and root from Z. fabago was carried out to detennine its contents from terpenoid compounds.